Why Do People Participate in Epidemiological Research? - Slegers, C.; Zion, D.; Glass, D.; Kelsall, H.; Fritschi, Lin; Brown, N.; Loff, B. (Springer, 2015)
Many assumptions are made about public willingness to participate in epidemiological research, yet few empirical studies have been conducted to ascertain whether such assumptions are correct. Our qualitative study of the public and of expert stakeholders leads us to suggest that people are generally prepared to participate in epidemiological research, particularly if it is conducted by a trusted public institution such as a government health department, charity, or university. However, there is widespread community distrust of research conducted or sponsored by pharmaceutical companies. Individuals are prompted to take part if the study concerns an illness they or a family member or friend have personally experienced or if they believe the research will confer a widespread public benefit. Preferences vary about the mode of contact for the research to be conducted. Willingness to participate in telephone surveys has decreased in recent years, and this may be a consequence of an increase in calls to homes by telemarketers and market researchers. Participants also stressed the importance of knowing where their names and contact details were sourced and suggested that this information be available to prospective study participants as a matter of course in the first approach or letter. We provide valuable information to epidemiologists in designing studies.